Wellbeing outcomes of lower income renters: a multilevel analysis of area effects - Parkinson, S.; Ong, Rachel; Cigdem, M. (Australian Housing and Urban Research Institute, 2014)
Project Summary - A key assumption behind area-based policies such as urban renewal and 'tenure mix' is to foster greater 'social mix' of communities to offset adverse consequences of concentrations of social disadvantage. This project sought to use statistical techniques to identify whether concentrations of social housing, diverse tenure mix or type or density of dwellings has effects on social wellbeing.